Covid-19 Control Measures by some community Pharmacies in Sulaimani City/Iraq - Kawa A. Obeid (Iraqi Journal of Pharmaceutical Sciences, 2023)
Background: Coronavirus pandemic (COVID-19) has enormously affected various healthcare services including the one of community pharmacy. The ramifications of these effects on Iraqi community pharmacies and the measures they have taken to tackle the spread of COVID-19 is yet to be explored. In this cross sectional survey, infection control measures by community pharmacies in Sulaimani city/Iraq has been investigated. Methods: Community pharmacists were randomly allocated to participate in a cross-sectional survey via visiting their pharmacies and filling up the questionnaire form. Results and discussion: A total of 50 pharmacies responded to the survey. Results showed that large numbers of community pharmacies (50%) have started to implement infection control measures during May 2020, three months after reporting the first COVID-29 cases in Iraq. The data shows that wearing face masks and washing hands frequently were among the most common personal measures to curb the spread of the virus with 33% each. Results reveal that 70% of the pharmacies sanitized customer’s space on a daily base and more than half of the participants install 1 meter distance measures between the customers. Meanwhile, almost half of the community pharmacies reduced the number of front line staff into one, minimising the risk of contact with infectious customers. Upon having a staff member testing positive, testing or self-isolation on all other staff members were imposed by the participants. Conclusion: Community pharmacists in Iraq were facing unprecedented challenge when coronavirus hit the country. Taking control measures by community pharmacies were of paramount significance to curb the spread of the virus in their working place and the community as well all these need a sophisticated plan in the future.